Meibomian gland dysfunction in patients with thyroid-associated ophthalmopathy: a systematic review and meta-analysis - Lu, Yanling; Li, Yongran; Lin, Tulong (Frontiers in Medicine, 2025)
BackgroundMeibomian gland dysfunction (MGD) secondary to thyroid-associated ophthalmopathy (TAO) represents a significant pathogenic mechanism in dry eye disease. This study provides the first systematic review and meta-analysis of MGD indicators in TAO.MethodsThe study protocol was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO) (Registration ID: CRD420251020327) before data extraction. Following PRISMA and MOOSE guidelines, a systematic search was conducted across PubMed, Embase, Web of Science, Scopus, Ovid Medline, and Cochrane from inception through March 27, 2025. Fourteen studies met the inclusion criteria. Key indicators included lipid layer thickness (LLT), meiboscore, meibum quality, first non-invasive tear film break-up time (NITBUT-f), average non-invasive tear film break-up time (NITBUT-avg), tear break-up time (TBUT), meibomian gland dropout area in the upper (MGDU) and lower eyelids (MGDL), and in vivo confocal microscopy (IVCM) markers (meibomian gland acinar density [MAD], meibomian gland acinar longest diameter [MALD], meibomian gland acinar shortest diameter [MASD]). Risk of bias was assessed using the AHRQ checklist or NOS. Meta-analysis was performed with Review Manager 5.4.1 and Stata 16.0. Publication bias was assessed using Egger's test and funnel plots. Fixed-effects models were used in the absence of significant heterogeneity (P > 0.10 or I2 < 50%); otherwise, random-effects models were applied.ResultsThirteen studies (813 TAO eyes, 522 controls) were included in the meta-analysis. Quality assessment revealed moderate-to-high methodological rigor across studies. Patients with TAO exhibited significantly worse meibomian gland indicators compared to controls: shorter tear film stability (NITBUT-f, TBUT), higher LLT, increased meiboscore and greater eyelid gland dropout (MGDU, MGDL). IVCM markers indicated meibomian acinar enlargement (MALD, MASD). Significant heterogeneity was observed in several outcomes, including NITBUT-f, NITBUT-avg, meiboscore, Meibum quality, TBUT and MGDU comparisons.ConclusionsDespite the limited number of studies and small sample sizes, TAO is linked to meibomian gland atrophy, acinar dilation, and tear film instability. Active disease is associated with more pronounced lipid layer abnormalities. Targeted evaluation and management of MGD are crucial to mitigate TAO-associated ocular surface morbidity and improve patient quality of life.